2021
DOI: 10.1111/cfs.12865
|View full text |Cite
|
Sign up to set email alerts
|

Trauma then and now: Implications of adoption reform for First Nations children

Abstract: Currently, Aboriginal children are significantly over-represented in the out-of-home-care system. Drawing on Aboriginal trauma scholarship and decolonizing methodologies, this paper situates the contemporary state removal of Aboriginal children against the backdrop of historical policies that actively sought to disrupt Aboriginal kinship and communities. The paper draws on submissions to the 2018 Australian Senate Parliamentary Inquiry into Adoption Reform from Aboriginal community controlled organizations and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Kinship processes play a fundamental role in First Nations child development (Bamblett et al, 2012; Turnbull‐Roberts et al, 2021; Krakouer et al, 2022). The Bringing them Home (BTH) report strived for the implementation of the ‘Indigenous Placement Principle’ hierarchy, where placements should be made in accordance with First Nations lore and engagement with Elders and community.…”
Section: Situating This Researchmentioning
confidence: 99%
“…Kinship processes play a fundamental role in First Nations child development (Bamblett et al, 2012; Turnbull‐Roberts et al, 2021; Krakouer et al, 2022). The Bringing them Home (BTH) report strived for the implementation of the ‘Indigenous Placement Principle’ hierarchy, where placements should be made in accordance with First Nations lore and engagement with Elders and community.…”
Section: Situating This Researchmentioning
confidence: 99%
“…Public schools that engaged children in learning traditional First Peoples languages found that this strengthened students’ development of cultural identity, pride, and self-worth, which increased their engagement in learning (Korff, 2019; Purdie et al, 2008). Furthermore, there is a convergence of evidence to show that children who are removed from their First Peoples culture have poor developmental and psychosocial outcomes (Australian Human Rights Commission, 1997; Cunneen & Libesman, 2000; Turnbull-Roberts et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Adopted people impacted by coercive attitudes and practices known as forced adoptions have reported psychological distress and identity problems (Kenny et al, 2013). Stolen Generations policies under the guise of concerns for children's well‐being resulted in individual and collective trauma and lost ties to family and culture (Human Rights and Equal Opportunity Commission, 1997; Newton, 2019; Turnbull‐Roberts et al, 2022). The Family Matters campaign has criticised the narrow legislative focus on legal permanency over relational permanency and cultural rights (SNAICC, 2021).…”
Section: Introductionmentioning
confidence: 99%